The emerging roles and mechanisms of exosomal non-coding RNAs in the mutual regulation between adipose tissue and other related tissues in obesity and metabolic diseases - Pan, Shifeng; Chen, Yongfang; Yan, Jie; Li, Fei; Chen, Xinyu; Xu, Xingyu; Xing, Hua (Frontiers in Endocrinology, 2022)
Exosomes (EXs) are the major types of extracellular vesicles (EVs) of ~20-200 nm diameter that can be secreted by most cells. EXs contain a variety of bioactive components (proteins, lipids, RNAs, etc.) and play important roles in regulating numerous biological processes under both physiological and pathological conditions. Throughout the studies in recent years, most studies have shown that EXs-derived non-coding RNAs (EXs-ncRNAs) are emerging as key players in cell-to-cell communication between metabolic organs in obesity and metabolic diseases. In this review, we will summarize recent findings about EXs-ncRNAs. In particular, we will focus on the following aspects: 1) the biogenesis and emerging roles of EXs, 2) the role of EXs-ncRNAs (EXs-miRNA, EXs-lncRNA, EXs-circRNA, etc.) that were secreted by adipose tissue-related tissues in influencing the differentiation of preadipocytes into fully functional mature adipocytes, and 3) the relationship between the adipose tissue derived EXs-ncRNAs and the development of insulin resistance, obesity and various cancers. This review aims to reveal the emerging roles and mechanisms of EXs-ncRNAs in the mutual cross-talk of adipose tissue and its related tissues, so as to provide a reference for elucidating the etiology of obesity and related metabolic diseases and screening novel therapeutic targets.